PENILAIAN RUANG BERMAIN ANAK DI KOTA DEPOK SEBAGAI SALAH SATU INDIKATOR TERCAPAINYA KOTA LAYAK ANAK - KARYA WIDYAWATI; RITA LAKSMITASARI (LPPM, 2015)
Under Regulation 38 and 41 of 2007, states that children must become a business issue provincial and regency / city. According to Revelation Hartomo, Deputy Growth, Ministry of Women Empowerment and Child Protection, said the City Proper Child program (KLA) is necessary for the district / city, due to global changes that threaten the child in terms of religious, social and cultural, human embryos that are reliable and formidable determine the future of the nation, as well as the child's risk of becoming victims of violence, harassment and discrimination. The existence of children's playground as one of the indicators of child-friendly cities need to be investigated existence. The purpose of this study was to determine the feasibility assessment of the children's playground in the number (quantity) and quality that will be achieved from the perspective of urban development of child-friendly cities. The target is to provide recommendations to the government on the needs of the children's playground in Depok area both in terms of quantity and quality in order to reach the Depok City of Eligible Children. The method used is to conduct a field survey and documentation of observations and interviews to see more detailed conditions. In conclusion existence Tapos playground in the district of Depok City has not facilitated standardized per RW Eligible Children ie there should be a playground. Needs to be cooperation between the government, and society in fulfillment staholder playground facilities in order to achieve the Depok City of Eligible Children. Keywords: Assessment, Children's playroom, Depok City, State Indicators of Eligible Children